2013
DOI: 10.5489/cuaj.820
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the metabolic profiles of diabetic and non-diabetic uric acid stone formers

Abstract: E190Cite as: Can Urol Assoc J 2013;7:E190-2. http://dx.doi.org/10.5489/cuaj.11133 Epub 2012 Mar 2. AbstractIntroduction: The aim of this study was to compare the metabolic profiles of diabetic and non-diabetic patients with uric acid stones to understand whether preventive strategies should be tailored to reflect different causative factors. Methods:The results of the metabolic evaluation of patients with uric acid stones identified prospectively from the Metabolic Stone Clinic at St. Joseph's Hospital, London… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…These conditions lead to increased risks of uric acid and calcium stone formation. 6,8,9 Urolithiasis as renal manifestations in gout patients usually is due to low urine pH. 10 Several studies have shown association between recurrent uric acid kidney stones and metabolic syndrome.…”
mentioning
confidence: 99%
“…These conditions lead to increased risks of uric acid and calcium stone formation. 6,8,9 Urolithiasis as renal manifestations in gout patients usually is due to low urine pH. 10 Several studies have shown association between recurrent uric acid kidney stones and metabolic syndrome.…”
mentioning
confidence: 99%